The big house - Coman, Carolyn; Shepperson, Rob (Asheville, N.C. : Front Street, 2004)
When Ivy and Ray's parents are sent to jail, and they are left in the custody of their parent's accusers, they decide to look for evidence that will "spring" their parents.
Keywords: Brothers and sisters -- Fiction; Detective and mystery stories; Humorous stories